Aspectos tecnológicos da evoluç\~ao produtiva do complexo químico brasileiro 1985-2009 - Luiz Dias Bahia; Bruno Rodrigues Pinheiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper tries to build and to analyze the evolution of technological indexes in Brazilian chemical industry during the 1985-2009 period. Our main conclusions are the following: the petrochemical emphasis of this industry has stood by; besides there have been an important technological development of the latter branches, but also of the non petrochemical ones.
Keywords: L65; D20; O33; 330; technological indexes; Brazilian industry; chemical supply chains